PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI, DAN PENGENDALIAN INTERNAL: TERHADAP KUALITAS LAPORAN KEUANGAN (STUDI EMPIRIS PT BANK BNI PERSERO TBK) (Jurnal Akuntansi, 2024)
This study analyzes the influence of Accounting Information System (AIS) implementation and Internal Control on the Quality of Financial Statements at PT Bank BNI (Persero) Tbk KCP Kramat. Using a quantitative associative approach with 86 valid responses, the research tests hypotheses via multiple linear regression grounded in agency and information theories. Findings demonstrate that both AIS and internal control, individually and simultaneously, exert a positive and significant impact on financial statement quality. The results suggest that integrating robust accounting technology with effective internal oversight is essential for enhancing the reliability, relevance, and timeliness of financial reporting amidst digital era challenges and internal fraud risks.